1993
DOI: 10.1007/bf03009631
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine attenuates the hypertensive response to tracheal intubation in pregnancy-induced hypertension

Abstract: Nifedipine attenuates the hypertensive response to tracheal intubation in pregnancy-induced hypertension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…If time permits, spinal is preferred over general anaesthesia to avoid the hypertensive response to intubation (attenuated by antihypertensives or opioids); spinal is, however, associated with lower cord pH and higher cord base deficit of uncertain clinical significance [414][415][416][417][418][419]. Spinals do not alter uteroplacental haemodynamics [420].…”
Section: General Principlesmentioning
confidence: 99%
“…If time permits, spinal is preferred over general anaesthesia to avoid the hypertensive response to intubation (attenuated by antihypertensives or opioids); spinal is, however, associated with lower cord pH and higher cord base deficit of uncertain clinical significance [414][415][416][417][418][419]. Spinals do not alter uteroplacental haemodynamics [420].…”
Section: General Principlesmentioning
confidence: 99%
“…Consequently, there is an increased risk of morbidity and mortality of both mother and baby (5). In order to reduce the occurrence and severity of these hemodynamic complications, many drugs such as hydralazine (6), magnesium sulfate (7), labetalol (8), fentanyl (5), trimethaphan (2), sodium nitroprusside (9), lidocaine (10), nitroglycerin (11,12), and nifedipine (13) have been used with varying degrees of success. Hydralazine has been the antihypertensive of choice for women with severe hypertension in pregnancy for many years (14,15).…”
Section: Attenuation Of Cardiovascular Response In Severe Preeclampsiamentioning
confidence: 99%
“…Short-acting sublingual nifedipine, a calcium channel blocker, is another effective antihypertensive agent that is sometimes used to control acute, severe hypertension in women with preeclampsia (16,17). Kumar et al (13) showed that sublingual nifedipine is effective in attenuating the hypertensive response to laryngoscopy and intubation in pregnancy-induced hypertension.…”
Section: Attenuation Of Cardiovascular Response In Severe Preeclampsiamentioning
confidence: 99%
“…Antihypertensive drugs in severe hypertension are useful before general anesthesia in decreasing the pressor response to tracheal intubation [75,76]. During labor, pain may be an important factor in increased blood pressur and should be controlled.…”
Section: Management Of Severe Hypertensionmentioning
confidence: 99%